The real cost of the external debt for the creditor and for the debtor - Carlos Massad (CEPAL Review, 1983)
In this article the author analyses the real cost of external debt servicing and reaches the conclusion that the cost in question is different for the creditor and for the debtor, nie former will normally take into account his own country’s financial market as a basis for evaluating the alternative use of his resources. In contrast, the debtor will have to take into consideration the real resources that he needs to use in his own country in order to generate foreign exchange for paying the debt.